PENGARUH AKUNTABILITAS DAN TRANSPARANSI TERHADAP KINERJA ANGGARAN BERKONSEP VALUE FOR MONEY PADA PEMERINTAH KOTA MALANG - Setia, Marselina Saina; Halim, Abdul; Setiyowati, Supami Wahyu (Jurnal Riset Mahasiswa Akuntansi, 2019)
This study aims to determine the effect of Accountability and Transparency on Budget Performance with Value For Money concept in Malang City Government. This research was conducted using quantitative methods, using explanatory research type explanatory research. The sampling method used was Purposive Sampling Technique, which was carried out on 50 Local Financial Staffs with data collection techniques through the distribution of questionnaires or questionnaires with the amount. While the data analysis technique in this study uses the classic assumption test technique and multiple linear regression statistical analysis. The results of this study indicate that simultaneous and partial Accountability and Transparency has a positive and significant effect on Budget Performance with a Value For Money concept. Accountability of financial statements in the City Government of Malang must be maintained and information relating to the results of the Government's budget performance is maintained or accountability is stated through the mass media honestly and openly so that the public can assess whether it has been effective and efficient results of Government performance. Budget Performance with the concept of value for money must be able to implemented and implemented well in order to improve the welfare of the community and the community will believe in the results of Government Performance, because public trust can also sustain the government to compete to become a good government. For further researchers, it is expected to add research variables other than that it is expected to use other methods besides distributing questionnaires such as interviews and observations so that the data obtained can be increased or more transparent.